Tradisi ciancui masyarakat Selatpanjang kabupaten Meranti terhadap adaptasi lingkungan - Jamallah Lillah; Siti Sofro Sidiq; Hesti Asriwandari (Program Studi Ilmu Lingkungan, Program Pascasarjana Universitas Riau, 2022)
The people of Selatpanjang, Meranti Islands Regency have a festival that is played to coincide with the celebration of the Chinese New Year, namely the Water War Festival (Cian Cui). This Water War Festival is played for six days before the peak event of the Chinese community in commemorating the Lunar New Year. Since 2013 this festival has been taken over by the local government and has become an annual festival. The equipment used when conducting this festival is a bucket, dipper, and a water gun. This festival begins after Asr and ends before Maghrib by circling the arena that has been prepared.This research is entitled Ciancui Tradition of Selatpanjang Community of Meranti Regency. The results of this study show and explain that the ciancui tradition in Selatpanjang has meaning in the Selatpanjang community itself, while the meaning of the ciancui tradition for the Selatpanjang community is that people consider ciancui as a culture, besides that they also perceive that ciancui has meaning as a business and ciancui is a identity of Selatpanjang itself. Although the ciancui tradition that was carried out was rejected, this tradition can still survive until now because in the implementation of the tradition, adjustments were made to the conditions of the community and there was a sense of openness to the Selatpanjang community.